2010
DOI: 10.1002/jso.21496
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative sentinel lymph node detection by vital dye through laparoscopy or laparotomy in early endometrial cancer

Abstract: SLNs detection rate is significantly higher through laparoscopy than through laparotomy after vital dye pericervical injection but intraoperative vital dye pericervical injection is not reliable as part of standard care for predicting lymphatic spread in women with early stage endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 31 publications
1
20
0
1
Order By: Relevance
“…The laparoscopic route seems to allow a higher SLN identification than laparotomy [6]. Mais et al evaluated 34 patients in a prospective cohort with the purpose of comparing SLN detection in laparoscopy vs laparotomy.…”
Section: Surgical Routementioning
confidence: 99%
See 4 more Smart Citations
“…The laparoscopic route seems to allow a higher SLN identification than laparotomy [6]. Mais et al evaluated 34 patients in a prospective cohort with the purpose of comparing SLN detection in laparoscopy vs laparotomy.…”
Section: Surgical Routementioning
confidence: 99%
“…The sentinel lymph node (SLN), by definition, is the first node to receive metastasizing cancer cells, as first described in 1960 by Gold et al for parotid cancer [6]. In 1996, Burke et al reported the SLN first application in EC [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations